Development of dairy products technology with application low-etherificated pectin products - Nabiyeva, Zhanar; Zhexenbay, Nurshash; Iskakova, Galiya; Kizatova, Maigul; Akhmetsadykova , Shynar (Eastern-European Journal of Enterprise Technologies, 2021)
The issue relatedto removing heavy and radioactive metals from the body is relevant all over the world. Chemical preparations for removing heavy metals and radionuclides are not effective enough, causing the depletion of trace elements in the body. It is effective to use substances contained in natural foods that do not cause side effects and provide for protective action. These substances include pectin, safe natural detoxifying agents that remove toxins from the body. When processing fruits and vegetables, pectin remains in the pomace thatis valuable for obtaining competitive products. There are techniques to produce pectin from plant raw materials by using enzymes that are harmless to health. The use of pectin concentrates in combination with dairy raw materials makes it possible to obtain biologically complete products with functional properties. A concentrate containing 5 %of pectin was used in the study reported in this paper. Raw materials were studied in terms of important indicators of their quality and safety, to determine their suitability and further use in yogurt technology. The formulations of yogurts have been devisedinvolving the application of low-esterified beet pectin concentrate, whose degree of etherification is 34.7 % and the complex-forming capacity is 290 mg Рb2+/g. It has been established that the most optimal sample contains pectin in the amount of 0.5 % per milk mass. To preserve the vitamin composition, the yogurts were prepared under the classic pasteurization regime of 72 to 75 °C with a 20 s aging. In the future, the industrial implementation of the devised technologies and formulations of pectin-containing dairy products could provide the population with products that have functional properties and contribute to the prevention of socially significant diseases